SN 2014C: A Metamorphic Supernova Exploded in the Intricate and Hydrogen-rich Surroundings - Zhai, Qian; Zhang, Jujia; Lin, Weili; Mazzali, Paolo; Pian, Elena; Benetti, Stefano; Tomasella, Lina; Liu, Jialian; Li, Liping (The Astrophysical journal, 2025)
We present photometric and spectroscopic observations of supernova (SN) SN 2014C, primarily emphasizing the initial month after the explosion at approximately daily intervals. During this time, it was classified as a Type Ib SN exhibiting a notably higher peak luminosity ( L peak  ≈ 4.3 × 10 42 erg s −1 ), a faster rise to brightness ( t rise  ≈ 11.6 days), and a more gradual dimming ( Δ m 15 V ≈ 0.48 mag) compared to typical Type Ib SNe. Analysis of the velocity evolution over the first ~20 days after the explosion supports the view that the absorption near 6200 Å is due to high-velocity H α in the outer layers of the ejecta, indicating the presence of a small amount of hydrogen in the envelope of the progenitor before the explosion. Assuming that the peak luminosity is entirely attributed to radioactive decay, we estimate that 0.14 M ⊙  of 56 Ni was synthesized in the explosion. However, this amount of nickel could no longer maintain observed brightness approximately 10 days after peak luminosity, suggesting additional energy sources beyond radioactive decay. This supplementary energy likely originates from interaction with the circumstellar medium (CSM). Consequently, the timing of the SN−CSM interaction in SN 2014C may occur much earlier than the emergence of Type IIn−like features during the nebular phase.